(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
This research aims to reveal the role of Iraqi universities in preventing drug abuse. The main issue revolves around understanding the contribution of universities in combating this phenomenon. The study, using descriptive and analytical methods, found that universities play a significant role in spreading awareness, conducting workshops on the dangers of drugs, and creating prevention programs for students. Additionally, universities should collaborate with the General Directorate for Drug Control in Iraq and encourage research to keep up with developments in drug prevention to protect students.